Decoding Chinese bilateral investment treaties / Shen Wei, Shanghai Jiao Tong University. - Shen, Wei, 1972- (Cambridge University Press, 2021)
This is a major work investigating China's bilateral investment treaties (BITs) regime through various approaches including textual analysis, case study, comparative study and empirical study. This book tries to unveil some of the puzzles in Chinese BITs. The general consensus is that the evolution of China's BIT regime has its underlying logic, which follows an investment liberalization trend and fits China's changing role from a key capital-importing state to a major capital-exporting state. A similar trend is evident in Chinese BIT-making and BIT policy. This book investigates these theoretical assumptions and looks into some of the loopholes in Chinese BITs.